HUBUNGAN PUSTAKAWAN DENGAN INFORMASI DAN UPAYA DALAM MENGELOLA LITERASI INFORMASI - Lusi ismail (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2021)
Librarians are people who are experts in the field of librarianship. Some aspects related to librarianship, one of which is the library. Theoretically, the library is an information institution that has several functions such as: information, book storage, research, education, recreation, and others. As library managers, librarians should be able to realize all library functions, so that their existence as an information institution can be felt by the information community. journals, dictionaries, encyclopedias, CDs, DVDs and other collections. In this paper, it can be concluded. First, librarians should understand how they relate to information, so that after they are about each other, they have the convenience of developing and processing them. Second, librarians have the ability to maximize the utilization of information in the library, such as by minimally procuring and disseminating information to the maximum. The three librarians understand information literacy so that librarians really provide information that is relevant to the needs of users and other information users.